Successful Intravenous Thrombolysis in Ischemic Stroke Caused by Tuberculous Meningitis: A Case Report - Peng, Xinke; Wu, Xiaomei; Lv, Lingling; Xiao, Qile; Zhan, Yajing; Wang, Chunyu; Zhang, Hainan (Frontiers in Neurology, 2021)
Tuberculous meningitis (TBM) has a variety of clinical manifestations and complications, and ischemic stroke is a common complication of TBM. However, there is no established prevention or treatment for stroke associated with TBM, and the safety and efficiency of thrombolysis in acute stroke caused by TBM remain unknown. Herein, we present a case of successful intravenous thrombolysis in ischemic stroke caused by TBM. A 50-year-old male patient with cerebral infarction had relevantly improved neurological function after intravenous thrombolysis, and he was subsequently found to have TBM. Our findings suggest that intravenous thrombolysis might be an effective acute treatment method for infectious stroke.